Ultrasensitive NO2Sensor Based on Ohmic Metal-Semiconductor Interfaces of Electrolytically Exfoliated Graphene/Flame-Spray-Made SnO2Nanoparticles Composite Operating at Low Temperatures - Nantikan Tammanoon (2018)
© 2015 American Chemical Society. In this work, flame-spray-made undoped SnO 2 nanoparticles were loaded with 0.1-5 wt % electrolytically exfoliated graphene and systematically studied for NO 2 sensing at low working temperatures. Characterizations by X-ray diffraction, transmission/scanning electron microscopy, and Raman and X-ray photoelectron spectroscopy indicated that high-quality multilayer graphene sheets with low oxygen content were widely distributed within spheriodal nanoparticles having polycrystalline tetragonal SnO 2 phase. The 10-20 μm thick sensing films fabricated by spin coating on Au/Al 2 O 3 substrates were tested toward NO 2 at operating temperatures ranging from 25 to 350 °C in dry air. Gas-sensing results showed that the optimal graphene loading level of 0.5 wt % provided an ultrahigh response of 26-342 toward 5 ppm of NO 2 with a short response time of 13 s and good recovery stabilization at a low optimal operating temperature of 150 °C. In addition, the optimal sensor also displayed high sensor response and relatively short response time of 171 and 7 min toward 5 ppm of NO 2 at room temperature (25 °C). Furthermore, the sensors displayed very high NO 2 selectivity against H 2 S, NH 3 , C 2 H 5 OH, H 2 , and H 2 O. Detailed mechanisms for the drastic NO 2 response enhancement by graphene were proposed on the basis of the formation of graphene-undoped SnO 2 ohmic metal-semiconductor junctions and accessible interfaces of graphene-SnO 2 nanoparticles. Therefore, the electrolytically exfoliated graphene-loaded FSP-made SnO 2 sensor is a highly promising candidate for fast, sensitive, and selective detection of NO 2 at low operating temperatures.